PERCEPTIONS OF MILLENIAL GENERATIONS IN JAKARTA TOWARDS TRADITIONAL FOOD OF BUGIS CAKES VIEW FROM A CULTURAL POINT - Antonius Rizki Krisnadi; Dhanik Puspita Sari; Bondan Pambudi; Jajang Gunawijaya; Nurbaeti (Bajang Institute, 2022)
Indonesia is very rich in cultural diversity. An example is a traditional food. The existence of conventional food has begun to shift with the entry of ethnic cuisine into Indonesia, especially the millennial generation who are more interested in modern food. This study aims to find out how the millennial generation in Jakarta views the traditional food of Bugis cake from a cultural point of view. The research methodology is quantitative descriptive research, and the data collection technique used is a questionnaire and literature study. Sampling was done by non-probability sampling and purposive sampling techniques. The sample of this research is 100 millennial generations in Jakarta who have ever consumed Bugis cake. The data analysis method uses single table analysis using frequency and percentage tables. The results showed that most of the perceptions of the millennial generation were in a positive category, 77%, while the negative was 4%, and the remaining 19% were neutral or average. This research concludes that most millennials know and understand the cultural elements of traditional Bugis cakes. The millennial generation will explore more about traditional food through books, websites or blogs. It is also hoped that the millennial generation can promote and make traditional food innovations so that traditional foods can keep up with the times.